ETHICAL AND SOCIAL ISSUES RELATED TO STUDENTS’ ACCESS TO HEALTHY FOOD IN THE UNIVERSITY CAMPUS. A THEORETICAL APPROACH - POP, Lavinia-Maria; IORGA, Magdalena; IOAN, Beatrice Gabriela (Studia Universitatis Babeş-Bolyai Bioethica, 2018)
University years represent a critical period in terms of establishing eating patterns and adapting to a new environment. The largest gain in weight occurs at age 18-29 and can have negative consequences on students` health status. The access of students to a healthy diet represents an ethical and social problem little studied in our country. The present paper wanted to examine the main causes that can lead to unhealthy patterns among students. The theoretic analysis showed that nutritional education, knowledge about food, health beliefs, academic schedule, campus food environment, financial incomes and meals’ costs - all these factors can have positive or negative influences on students’ eating habits. In addition, international students represent a more vulnerable population and one of the main sources of stress of acculturation among international students is represented by the type of food from hosting culture. Given the above, universities must take an attitude and contribute to the development of a healthy university food environment. Implementation of dietary programs to improve the nutritional health of students will inform the student who will be more aware of the consequences of unhealthy foods, poor in vegetables and fruits on mental and physical health, later in life. In conclusion, there are many factors that affect the eating habits among students, It is really useful to know about these factors in order to provide effective education and nutritional care so university must offer equal access to healthy food to all of its students. REZUMAT. Probleme etice și sociale privind accesul studenților la alimentele sănătoase în campusurile universitare. O abordare teoretică. Anii universitari reprezintă o perioadă critică în ceea ce privește stabilirea tiparelor alimentare și adaptarea la un nou mediu. Cel mai mare câștig în greutate apare la vârste cuprinde între 18-29 de ani și poate avea consecințe negative asupra stării de sănătate a studenților. Accesul studenților la o dietă sănătoasă reprezintă o problemă etică și social, puțin studiată în țara noastră. Din acest punct de vedere, această lucrare a dorit să examineze principalele cauze care pot duce la tipare nesănătoase în rândul studenților. Analiza descrisă în acest articol arată că educația nutrițională, cunoștințele despre alimente, credințele în sănătate, programul academic, mediul alimentar din campus, veniturile financiare și costurile meselor - toți acești factori pot avea influențe pozitive sau negative asupra obiceiurilor alimentare. Studenții internaționali reprezintă o populație și mai vulnerabilă, iar una dintre principalele surse de stres aculturativ în rândul studenților internaționali este reprezentată de tipul de mâncare din țara gazdă. Universitățile trebuie să ia atitudine și să contribuie la dezvoltarea unui mediu alimentar universitar sănătos. Implementarea programelor alimentare pentru îmbunătățirea sănătății nutriționale a studenților vor contribui la informarea studentului care va fi mai conștient de consecințele alimentelor nesănătoase, sărace în legume și fructe, asupra sănătății mintale și fizice, ulterior în viață. În concluzie, există mulți factori care afectează obiceiurile alimentare în rândul studenților și este foarte util să cunoaștem acești factori pentru a oferi studenților educație și îngrijire nutrițională eficientă iar universitățile să faciliteze accesul egal al studenților la o mâncare sănătoasă. Cuvinte cheie: student, nutriție, etică, universitate, sănătate, vulnerabilitate, tabieturi alimentare, studenți internaționali.